2020
DOI: 10.4038/jsc.v11i2.27
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer activity of <em>Fluggea leucopyrus</em> willd (Katupila) against human ovarian carcinoma and characterization of active compounds

Abstract: Fluggea leucopyrus Willd has been used in the treatment for cancers in the traditional system of medicine in Sri Lanka. This study was aimed on evaluation of anti-cancer activity of F.leucopyrus against Human Ovarian carcinoma and identification of active compounds. Anti-cancer activity of ethyl acetate (EtoAc) extract of leaves and two compounds isolated from EtoAc extract were evaluated using MTS and hTERT assays on Human Ovarian carcinoma (A 2780). MTS assay showed a significant anti-proliferation activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Bulugahapitiya et al, 2020 has reported that the leaves of the F. leucopyrus plant contains a Bergenin isomer which is responsible for the anticancer activity (Bulugahapitiya et al, 2020). Anticancer activity also has been detected for the bark and aerial parts of this plant (Bulugahapitiya et al, 2020). Further report suggest that bergenin could be used to develop more potent galectin-3 inhibitors which is a anticancer mechanism (Jayakody et al, 2018, Stegmayr et al, 2019.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bulugahapitiya et al, 2020 has reported that the leaves of the F. leucopyrus plant contains a Bergenin isomer which is responsible for the anticancer activity (Bulugahapitiya et al, 2020). Anticancer activity also has been detected for the bark and aerial parts of this plant (Bulugahapitiya et al, 2020). Further report suggest that bergenin could be used to develop more potent galectin-3 inhibitors which is a anticancer mechanism (Jayakody et al, 2018, Stegmayr et al, 2019.…”
Section: Discussionmentioning
confidence: 95%
“…Current study determined that the practitioners used whole plant, roots and leaves. Bulugahapitiya et al, 2020 has reported that the leaves of the F. leucopyrus plant contains a Bergenin isomer which is responsible for the anticancer activity (Bulugahapitiya et al, 2020). Anticancer activity also has been detected for the bark and aerial parts of this plant (Bulugahapitiya et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the methanolic extract of B. monnieri dissolved in 0.1% DMSO exhibited the highest toxicity, while P. amboinicus demonstrated the least toxicity. According to [37], the brine shrimp lethality assay for the ethyl acetate extract of F. leucopyrus revealed LC50 values of 2779.63 μg/mL, suggesting no toxicity of the plant extract towards brine shrimp. This implies that LC50 values can vary with differences in plant extraction methods.…”
Section: Evaluation Of the Toxicity Of Methanolic Plant Extracts Diss...mentioning
confidence: 99%
“…The IC 50 of pure bergenin isolated from different parts of plant species ( Table 2 ) was determined against P. falciparum in vitro, with the following results: 2.41–14.1 µg/mL [ 37 , 38 , 40 , 50 , 58 , 103 ]. The mechanism of action by which bergenin inhibits the growth of the parasite in vitro is not yet well known, but it is suggested that it is triggered by the inhibition of polymerization of the heme group of the parasite in a similar way to the mechanism of action of artemisinin since both are lactones of the same family [ 39 , 104 ].…”
Section: Biological and Pharmacological Activities Of Bergeninmentioning
confidence: 99%
“…Bulugahapitiya et al [ 40 ] reported anticancer activity of ethyl acetate extract (Et O Ac) from F. leucopyrus leaves, bergenin and bergenin diastereomer (at C-9 and C-14) both isolated from Et O Ac, against human ovarian carcinoma. Anticancer activity was evaluated using cell proliferation assays (MTS) and human telomerase reverse transcriptase (hTERT) in human ovarian carcinoma (A 2780).…”
Section: Biological and Pharmacological Activities Of Bergeninmentioning
confidence: 99%